The determinants of working capital management: the contextual role of enterprise size and enterprise age - Nastiti, Pambayun Kinasih Yekti; Atahau, Apriani Dorkas Rambu; Supramono, Supramono (Business, Management and Economics Engineering, 2019)
Purpose – working capital management plays a vital role in determining the continuity of enterprises’ business activities. Enterprises should manage their working capital efficiently to avoid excessive working capital investments and at the same time, to maintain their liquidity. This study aims to examine the determinants of working capital management and to test the different effects of the determinants of working capital management based on enterprise size and enterprise age. Research methodology – the sample consists of 117 manufacturing enterprises listed at the Indonesian Stock Exchange for the years 2010–2017. Panel data regression was used to test the hypothesis. Findings – the findings reveal that sales growth and economic growth determine working capital management. However, the effects of the determinants of working capital management differ depending on enterprise size and enterprise age. Specifically, economic growth is the only determinant that exhibits different effects on working capital management between different enterprise size and enterprise age subsamples. Meanwhile, besides economic growth, capital expenditure, and operating cash flow are the other enterprise-specific determinants that exhibit different effects on working capital management between the two enterprise age subsamples. Research limitations – this study only measures enterprise size with total assets. Thus, we advise future studies to complement this proxy with other measures such as market value and the listing size criterion (main board vs development board). Further, it is necessary to analyse the non-linear relationship between leverage and working capital management to explain the positive effect of leverage on working capital management. Practical implications – the empirical results suggest that manufacturing enterprises must focus more on their sales growth because it affects their ability to manage their working capital efficiently. Besides, younger manufacturing enterprises need to shorten their cash cycles that are longer relative to old enterprises. Originality/Value – no previous studies have analysed the determinants of working capital management based on enterprise characteristics, especially enterprise size and age. Specifically, in the scientific literature, enterprise size and enterprise age mainly act as the dependent variables.